Verbal behaviour and perspective analysis: the second language learning context. - Figueiredo, Sandra (2018)
The scientific discussion in the second language learning area is very recent and less structured than the literature developed as part of the investigation into the first language acquisition subject (Ricthie & Bhatia, 1996), especially not observed in the Portuguese domain, regarding the second language acquisition and, in other hand, with respect to the specific level of cognition achievement. First, theorize about the language development as human skill and ability, becomes easier within the knowledge of the language disorders with brain areas determined, good predictions, identification of causes and concepts formulation that directly applies to a public more or less clearly defined. Secondly, theorize about the normative language development and linguistic decoding generates less consensus among theorists and researchers in the area. On the issue of second language acquisition the controversy becomes by itself a prerequisite for the literature and empirical studies development. It is very important scientifically and, above all, on a social way (pedagogical application) to produce knowledge and suggest solutions enabling an answer to the main research problem of this PhD project: “How to identify and thereby develop prevention methods addressed to overcome learning disabilities of children, adolescents and adults, second language learners, in academic context, taking into account the premise of different cognitive performance (at the highest level of ability and skill) and, verbal behavior, determined by psychological, cognitive and linguistic factors? We started by developing a tests battery to assess reaction time and accuracy on Portuguese Second Language